Prevalence and Risk Factors of Diabetes Mellitus in Primary Care Setting in Low Income Countries: A Comprehensive Systematic Review - Pambajeng, Cesil Raras; Stephanie (The International Journal of Medical Science and Health Research, 2024)
Background: Primary diabetes management involves maintaining glycemic control, crucial for minimizing complications and mortality. To achieve Sustainable Development Goal 3.4, improved diabetes treatment availability in primary care facilities is essential. Methods: Adhering to the PRISMA 2020 principles, this systematic review focused on examining complete English literature texts published from 2014 to 2024. Several websites, such as ScienceDirect, PubMed, and SagePub, were used to collect the literature. Result: Following the decision to subject eight publications to further research, a comprehensive evaluation of the complete literature was conducted. Conclusion: Diabetes mellitus prevalence in low-income countries is significantly higher than in other countries, largely due to factors like older age, high waist-to-hip ratio, family history, and unhealthy diet. The unmet need for diabetes care is high, with 77% not receiving necessary care, especially in primary settings. Policy changes and raising awareness are crucial to address the global diabetes epidemic.